The Role of Internal Audit in The Merger and Acquisition Process to Provide Added Value: A Critical Review - Yuwono, Matias Andika; Ellitan, Lena (Shafin: Sharia Finance and Accounting Journal, 2024)
Purpose â€“ This research focuses on how internal audit influences added value in the merger and acquisition (M&A) process. One of the internal audits provides value added by doing due process diligence For M&A transactions. The failure rate in creating value for companies and shareholders through M&A is still relatively high. Factors contributing to such failures include cultural differences between organizations, overly optimistic decisions based on market assessments, overestimating synergies, and inappropriate technology assessments. In overcoming these risks, the role of internal audit becomes crucial. This research underscores how internal audits can aid in recognizing and addressing the risks linked to M&A, particularly during the strategy, feasibility assessment, and results integration implementation phases. Methodology â€“ This research uses descriptive qualitative analysis methods Findings â€“ Research demonstrates that internal audit plays a vital role in guaranteeing the seamless operation of the M&A process. Internal audits help identify the various risks involved in the M&A process, from market and financial risks to legal and cultural risks. In addition, internal audits also provide recommendations for improvements needed to ensure that the M&A process runs according to the company’s plans and goals. Thus, the contribution of internal audit is significant in ensuring the success of every M&A transaction carried out by the company. Originality â€“ This article comprehensively discusses internal audit activities in the M&A process so the internal audit activity can add value to the company.